Genetic dissection of QTLs for starch content in four maize DH populations - Zhang, Xiaolei; Wang, Min; Zhang, Changzheng; Dai, Changjun; Guan, Haitao; Zhang, Ruiying (Frontiers in Plant Science, 2022)
As the principal carbohydrate source, starch is the main component of maize kernels. Understanding the genetic basis of starch content (SC) benefits greatly improving maize yield and optimizing end-use quality. Here, four double haploid (DH) populations were generated and used to identify quantitative trait loci (QTL) associated with SC. The phenotype of SC exhibited continuously and approximately normal distribution in each population. A total of 13 QTLs for SC in maize kernels were detected in a range of 3.65-16.18% of phenotypic variation explained (PVE). Among those, only some were partly overlapped with QTLs previously known being related to SC. Meanwhile, twelve genes encoding key enzymes in maize starch metabolism locate within QTLs identified in this study. These QTLs will pave a path to explore candidate genes regulating SC in maize kernel, and facilitate breeding program based on molecular marker-assisted selection to cultivate maize varieties with an ideal and proper grain quality.